Association between depression, anxiety, and stress with sleep quality in Indonesian people during the COVID-19 pandemic - Argo, Teresa Mika; Kurniawan, Andree; Liem, Jean Andrina; Sugianto, Jeremy Octavian; Michael, Rafael Jonathan; Agatha, Lisa; Tanuwijaya, Nathania Victoria Stevina; Wonsono, Beverley; Rivami, Dwi Savitri (Public Health of Indonesia, 2021)
Background: To prevent the spread of COVID-19, authorities implemented health protocols such as quarantine, large-scale social restrictions, and lockdowns. Data on the psychological effects and sleep quality as a result of these health protocols are still limited.Objective: This study was aimed to determine the association between depression, anxiety, and stress with sleep quality during the COVID-19 pandemic in Indonesia.Methods: An online survey was used to do a cross-sectional study among students in Indonesia. Sociodemographic information, including age, gender, religion, level of education, and regions, was analyzed. Levels of depression, anxiety, and stress were measured using the DASS-21 questionnaire. Sleep quality was determined using Pittsburgh Sleeping Quality Index (PSQI) questionnaire. Chi-square was used to evaluate the variables for bivariate analysis and logistic regression for multivariate analysis.Results: A total of 913 participants from across Indonesia included to this study. Adolescent (OR=0.367, 95% CI=0.199-0.679), female (OR=1.437, 95% CI=1.095-1.886), and high school students (OR= 0.737, 95% CI=0.544-0.999) had a higher risk for having poor sleep quality. In the multivariate analysis there were significant relationship between sleep quality with depression (Adjusted OR= 1.887, 95% CI=1.330-2.679), anxiety (Adjusted OR=1.731, 95% CI=1.221-2.455), stress (Adjusted OR= 2.577, 95% CI=1.617-4.107), use of sleeping medication (Adjusted OR=9.070, 95% CI=2.062-39.896) and age (Adjusted OR= 0.414, 95% CI= 0.205-0.837).Conclusion: There was an association between depression, anxiety, stress, consumption of sleeping medication, age, and poor sleep quality during the pandemic in Indonesia.